Effect of tumor cells and tumor microenvironment on NK‐cell function. Issue 6 (June 2014) - Vitale, Massimo; Cantoni, Claudia; Pietra, Gabriella; Mingari, Maria Cristina; Moretta, Lorenzo
<x xml:space="preserve">Abstract</x> The ability of tumors to manage an immune‐mediated attack has been recently included in the "next generation" of cancer hallmarks. In solid tumors, the microenvironment that is generated during the first steps of tumor development has a pivotal role in immune regulation. An intricate net of cross‐interactions occurring between tumor components, stromal cells, and resident or recruited immune cells skews the possible acute inflammatory response toward an aberrant ineffective chronic inflammatory status that favors the evasion from the host's defenses. Natural killer (NK) cells have powerful cytotoxic activity, but their activity may be eluded by the tumor microenvironment. Immunosubversion, immunoediting or immunoselection of poorly immunogenic tumor cells and interference with tumor infiltration play a major role in evading NK‐cell responses to tumors. Tumor cells, tumor‐associated fibroblasts and tumor‐induced aberrant immune cells (i.e. tolerogenic or suppressive macrophages, dendritic cells (DCs) and T cells) can interfere with NK‐cell activation pathways or the complex receptor array that regulate NK‐cell activation and antitumor activity. Thus, the definition of tumor microenvironment‐related immunosuppressive factors, along with the identification of new classes of tissue‐residing NK‐like innate lymphoid cells, represent key issues to design effective NK‐cell‐based therapies of solid tumors.